STRATEGI FLA MENDORONG NESTLÉ MELAKUKAN CSR DALAM BIDANG PEKERJA ANAK DI PANTAI GADING PADA TAHUN 2012-2017 - Alvina, Vivi; Wiranata, I Made Anom; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2021)
ABSTRACT This research aims to describe the strategy of a non-governmental organization, named the Fair Labor Association (FLA) to encourage Nestlé to make behavioral changes by using qualitative methods. The problem of child labor in Ivory Coast has become a complicated issues that need to be solved. As one of the largest food companies in the world and for supplying cocoa from the Ivory Coast, Nestlé has an important role in combating child labor issues. However, Nestlé has not been able to reduce the number of child labor in Ivory Coast. Therefore, the researcher uses the conceptual framework of private authority theory and the strategy of non-governmental organizations in encouraging companies to do Corporate Social Responsibility (CSR). This research can then see that FLA's auditing and reporting strategies can help Nestlé and Ivory Coast reduce child labor numbers and create a better life for the society than before. Keywords: Ivory Coast, Child Labor, Private Authority, NGO Strategy.